Austenitic high interstitial steels vs. CoCrMo – Comparison of fatigue behavior. (June 2015) - Gueler, Sedat; Schymura, Michael; Fischer, Alfons
Highlights: Endurance limit of CoCrMo0.25 equals 650 MPa at the εa, t of 0.3%. AHIS CN0.96 reaches the σD of 390 MPa at the same εa, t of 0.2% as CoCrMo0.03. Co-base alloys show strain induced phase transformation and strain induced twinning. CrMnCN steels predominantly appear to show strain induced twinning. SFE and the content of interstitial alloying elements are the key property for the endurance behavior. Abstract: The favourable combination of strength and ductility as well as excellent corrosion resistance of CrNiCN-austenitic steels is the reason for their use in biomedical engineering. However, Ni was attributed to cause allergies within a certain number of patients. Thus Ni-free alternatives like CoCrMo- and Ti-base alloys are often preferred. Other possible alternatives might be austenitic high nitrogen steels (AHNS) and austenitic high interstitial steels (AHIS). The aim of this study is to compare the fatigue properties of Ni-free austenitic CrMn(Mo)CN-steels with 0.85–1.07 wt% C + N, CoCrMo-alloy with up to 0.25 wt% C and conventional CrNiCN-steels with 0.01–0.42 wt% C + N. The comparison was conducted using total strain controlled axial LCF and HCF fatigue tests at room temperature on solution-annealed samples. After mechanical testing the samples were investigated by means of SEM including EBSD and TEM in order to analyse the distribution of plastic strains. In contrast to the CrNiCN-steels, which show cyclic hardening before the generation of the first crack, the CrMn(Mo)CN as well as the CoCrMo-alloys only showed cyclic softening. Still within the HCF regime the Co-base alloys showed the best fatigue behavior in terms of numbers of cycles to fracture Nf for a given total strain amplitude, while the Ni-free CrMn(Mo)CN-steels were either as good or slightly worse. The results indicate a distinct correlation between slip behavior, stacking fault energy and the amount of interstitials in solid solution.